Unraveling the interplay: exploring signaling pathways in pancreatic cancer in the context of pancreatic embryogenesis - Swain, Sashikanta; Narayan, Ravi Kant; Mishra, Pravash Ranjan (Frontiers in Cell and Developmental Biology, 2024)
Pancreatic cancer continues to be a deadly disease because of its delayed diagnosis and aggressive tumor biology. Oncogenes and risk factors are being reported to influence the signaling pathways involved in pancreatic embryogenesis leading to pancreatic cancer genesis. Although studies using rodent models have yielded insightful information, the scarcity of human pancreatic tissue has made it difficult to comprehend how the human pancreas develops. Transcription factors like IPF1/PDX1, HLXB9, PBX1, MEIS, Islet-1, and signaling pathways, including Hedgehog, TGF-β, and Notch, are directing pancreatic organogenesis. Any derangements in the above pathways may lead to pancreatic cancer.TP53 and CDKN2A are tumor suppressor genes, and the mutations in TP53 and somatic loss of CDKN2A are the drivers of pancreatic cancer. This review clarifies the complex signaling mechanism involved in pancreatic cancer, the same signaling pathways in pancreas development, the current therapeutic approach targeting signaling molecules, and the mechanism of action of risk factors in promoting pancreatic cancer.